A Generalization of Ciric Quasi-Contractions for Maps on S-Metric Spaces: Nguyen Trung Hieu, Nguyen Thi Thanh Ly, Nguyen Van Dung - Team, Support (Thai Journal of Mathematics, 2015)
In this paper, we prove a fixed point theorem for a class of maps on S-metric spaces. As applications, we get the fixed point theorems in [1] and [2]. Also, examples are given to analyze the results.